An investigation of Internet Service Provider selection criteria: A systematic literature review - Naji M.; Thiruchelvam S.; Khudari M. (College of Education, Al-Iraqia University, 2024)
In todays highly competitive business environment, organizations need to collaborate with strategic partners to provide high quality services at lower cost to maintain their effectiveness and efficiency. Hence, the concept of Supply Chain Management (SCM) emerged to effectively coordinate and manage financial, physical, and information activities within organizations and among all participating external parties. Qualitative and quantitative factors must be considered in SCM to ensure sustainable development. The research investigates the metrics and criteria influencing the process of selecting an Internet service provider (ISP) from 2001 to 2022 to assess the extent to which these factors have met the requirements of current decision-makers. It is appropriate to conduct a literature review in light of the changes in the purchasing process and determine its suitability for choosing an ISP. A comprehensive literature review of 51 articles published during the above period was conducted to ensure coverage of the latest ISP selection criteria. The results indicate a decline in the importance of criteria related to cost and prices and an increase in the importance of criteria such as quality, reliability, and performance, as evidenced by their repeated mention in the literature. The Author(s) 2023.